PERFORMANCE ASSESSMENT OF MICROFINANCE BANKS IN NIGERIA: A CASE STUDY OF SELECTED MICROFINANCE BANKS (IN ADAMAWA STATE) - Nidiya, Sani Adamu; Isa, Dominic Dzari; Fwah, Bensley Benedict T. (IJRDO - Journal of Business Management, 2022)
This study undertakes to assess the performance of selected Microfinance Banks in Adamawa State over time with a view to evaluate their structure, objectives, and practicability as it affects their functions. The study also depicts customers’ and staffs’ profile of MFB in the selected areas so as to know whether or not their input had affected the performance of the MFB. In the same vein, it analyzed and evaluates the causes of failure of those banks in the study area and suggested solutions to ameliorate the problems identified. The method of data collected was based on the use of both descriptive survey and analytical presentation. The study revealed that generally the liquidity position of MFB was weak as it was about 0.96 in 2007 and 0.88 in 2008 as against 2.00 (i.e. standard recommended for the industry). Similarly, the debt equity ratio revealed that these banks rely heavily on borrowed capital, hence, if for any reason the creditors withdraw their funds, the banks would be faced with a situation of imminent collapse. Similarly, there are strong relationships between their capital base, liquidity stability and relative income. It is thus concluded, therefore, that there is the need for greater cooperation between the central bank of Nigeria (CBN) and Nigeria Deposit Insurance Cooperation (NDIC).